Biodiversity and ecosystem services in the Campo Rupestre: A road map for the sustainability of the hottest Brazilian biodiversity hotspot - Fernandes, G. Wilson; Arantes-Garcia, Lucas; Barbosa, Milton; Barbosa, Newton P.U.; Batista, Eugênia K.L.; Beiroz, Wallace; Resende, Fernando M.; Abrahão, Anna; Almada, Emmanuel D.; Alves, Elaine; Alves, Natacha J.; Angrisano, Patrícia; et al. (Elsevier, 2020)
Global sustainability rests on a myriad of benefits provided by natural ecosystems that support human livelihoods and well-being, from biodiversity persistence to climate regulation. The undeniable importance of conserving tropical forests has drawn most of the conservation spotlight towards it. However, open ecosystems such as the Brazilian Campo Rupestre (rupestrian grassland), have been historically overlooked despite their high diversity and key associated ecosystem services. We highlight major current threats to the persistence of the Campo Rupestre emphasizing its ecological, social, cultural, geo-environmental, and economic importance. We call attention to the importance of the Campo Rupestre as a reservoir of biodiversity and ecosystem services and offer priority actions that resulted from discussions involving scientists, industry representatives, environmental managers, and other members of civil society. Proposed actions include efforts related to ecological restoration, sustainable ecotourism, protection of traditional ecological knowledge, identification of emerging research questions, and development of tailored public policies. Such issues are integrated into a framework that collectively represents a road map to safeguard the Campo Rupestre from further degradation and steer its historical overexploitation towards sustainable management. Safeguarding the future of non-forest biomes like this poses a challenge to current paradigms of nature conservation. By establishing priorities and guidelines, we propose an actionable plan, which we hope can support informed decision-making policy towards a sustainable use of the Campo Rupestre.
Keywords: Biodiversity conservation; Bioeconomy; Global change; Mountain ecology; Policy; Rupestrian grassland